The carboxylate-releasing phosphorus-mobilizing strategy can be proxied by foliar manganese concentration in a large set of chickpea germplasm under low phosphorus supply - Pang, Jiayin; Bansal, Ruchi; Zhao, Hongxia; Bohuon, Emilien; Lambers, Hans; Ryan, Megan H.; Ranathunge, Kosala; Siddique, Kadambot H. M. (The New phytologist, 2018)
Root foraging and root physiology such as exudation of carboxylates into the rhizosphere are important strategies for plant phosphorus (P) acquisition. We used 100 chickpea (Cicer arietinum) genotypes with diverse genetic backgrounds to study the relative roles of root morphology and physiology in P acquisition. Plants were grown in pots in a low-P sterilized river sand supplied with 10 μg P g−1 soil as FePO4, a poorly soluble form of P. There was a large genotypic variation in root morphology (total root length, root surface area, mean root diameter, specific root length and root hair length), and root physiology (rhizosheath pH, carboxylates and acid phosphatase activity). Shoot P content was correlated with total root length, root surface area and total carboxylates per plant, particularly malonate. A positive correlation was found between mature leaf manganese (Mn) concentration and carboxylate amount in rhizosheath relative to root DW. This is the first study to demonstrate that the mature leaf Mn concentration can be used as an easily measurable proxy for the assessment of belowground carboxylate-releasing processes in a range of chickpea genotypes grown under low-P, and therefore offers an important breeding trait, with potential application in other crops.